Analysis of weight distribution strategies in unilateral transtibial amputees during the stand-to-sit activity. Issue 1 (2nd January 2016) - Agrawal, Vibhor; O'Toole, Christopher; Gaunaurd, Ignacio A.; Gailey, Robert S.
Abstract : Current methods of quantifying the stand-to-sit activity (StTS) are resource intensive and have not been applied to unilateral transtibial amputees (TTAs). The purpose of this study is to define five phases of arm-rest assisted and unassisted StTS using simple instrumentation and implement this method for assessing TTA movement patterns. Twelve TTAs and 12 age-matched non-amputees performed StTS with and without arm-rest support. Symmetry of weight distribution between lower limbs was calculated for five StTS phases: Descent Initiation; Descent Deceleration; Seat-Contact; Stabilisation and Sitting. TTAs demonstrated an asymmetrical weight distribution pattern and a tendency to transfer weight to the intact limb during the course of the activity. Non-amputees had relatively higher symmetry and did not exhibit substantial weight shifts during the activity. Symmetry indices were similar for assisted and unassisted sitting in both subject groups. These results highlight a need for therapeutic interventions in TTAs for reducing loading asymmetries and associated co-morbidities. Abstract : Practitioner Summary: This study defines a novel method for quantifying stand-to-sit movements using clinically friendly equipment and is the first to investigate the stand-to-sit activity of unilateral transtibial amputees. The observed differences in inter-limb weight distribution strategies between amputees and non-amputees could provide insights for clinical assessment and intervention.